Occurrence, trophic transfer, and health risk assessment of bisphenol analogues in seafood from the Persian Gulf. (May 2020) - Akhbarizadeh, Razegheh; Moore, Farid; Monteiro, Carolina; Fernandes, José O.; Cunha, Sara C.
Abstract: The presence of chemicals in marine organisms is an important issue for human health due to the growing rate of seafood consumption. Potential exposure to seven bisphenol analogues through seafood consumption was investigated in some popular seafood from the Persian Gulf. Bisphenols were analyzed by gas chromatography–mass spectrometry. Bisphenol A (BPA) and bisphenol B (BPB) were the first and second most common bisphenols in the studied samples, respectively. The highest levels of BPA (mean 13.58 ± 5.70 μg/kg.dw) and BPB (mean 10.30 ± 7.98 μg/kg.dw) were found in E.coioides species. Bisphenol F and bisphenol AF were detected only in P. armatus and L. klunzingeri, respectively . Trophic transfer investigation demonstrated that BPA and BPB were biomagnified in the studied organisms through their diet. The eco-toxicity and estrogenic risk assessment indicated that seafood consumption does not pose a health threat to consumers. However, routine monitoring of bisphenols in seafood seems to be necessary to ensure food safety. Graphical abstract: Unlabelled Image Highlights: Presence of 7 bisphenol analogues was investigated in seafood from the Persian Gulf. BPA and BPB was the first and second most common bisphenols, respectively. BPE, BPZ, and BPAP were not detected in analyzed sample. BPA and BPB were possibly biomagnified in the studied organisms through their diet. Hazard ratio and estrogenic effects of BPs intake via seafood consumption was low.